1995
DOI: 10.1116/1.579759
|View full text |Cite
|
Sign up to set email alerts
|

Surface phase transformations in the Ni/Si(111) system observed in real time using low-energy electron microscopy

Abstract: Epitaxial surface of NiSi2(001) studied with lowenergy electron diffraction and scanning tunneling microscopy Thinfilm crystallography using reflection highenergy electron diffraction ''rod intensity profiles'': Ni/Si(111) Submonolayer Ni deposits quenched from above 840°C produce an ''impurity stabilized'' 1ϫ1 phase, which scanning tunnel microscope observations reveal to be a 1ϫ1 lattice gas of ring clusters ͑RCs͒ together with Si adatoms in local 2ϫ2 domains. We call this phase 1ϫ1-RC. Real time low-energy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(7 citation statements)
references
References 15 publications
(21 reference statements)
1
6
0
Order By: Relevance
“…The growth mode of the ͑1 3 1͒-RC structure indicates limited solubility of RC's in regions of the ordered ͑7 3 7͒ phase. We have earlier observed a qualitatively similar separation for Ni͞Si(111) [4]. p 7 ͒ as gray at these conditions.…”
supporting
confidence: 76%
See 1 more Smart Citation
“…The growth mode of the ͑1 3 1͒-RC structure indicates limited solubility of RC's in regions of the ordered ͑7 3 7͒ phase. We have earlier observed a qualitatively similar separation for Ni͞Si(111) [4]. p 7 ͒ as gray at these conditions.…”
supporting
confidence: 76%
“…The principle of operation of the LEEM is described in detail elsewhere [2], as is the microscope used in this work [4]. The base pressure in the instrument was 2 3 10 210 torr.…”
mentioning
confidence: 99%
“…19 -R23.4°, and (1 × 1)-ring cluster (RC) phases. [7][8][9][10][11][12][13][14][15][16][17][18][19][20] These surface silicides are thought to be intermediate states before the formation of thick epitaxial silicides. It has been reported that ´n 2 and 2 2-R45°phases form on a Si(100) substrate depending on the Ni coverages and substrate temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…Several 2D phases are reported to appear during the reaction of an ultrathin Ni film with a Si (111) substrate, ( phases [13][14][15][16][17]. The last two phases are the most likely intermediate steps to epitaxial growth of 3D NiSi 2 onto Si (111) [18,19,20]. On Si (001), depending on the Ni coverage and thermal annealing conditions, several nickel-silicide compounds can be formed [22].…”
Section: Introductionmentioning
confidence: 99%